Human Mesenchymal Stem Cell-Derived Microvesicles Prevent the Rupture of Intracranial Aneurysm in Part by Suppression of Mast Cell Activation via a PGE2-Dependent Mechanism. (8th July 2016) - Liu, Jia; Kuwabara, Atsushi; Kamio, Yoshinobu; Hu, Shuling; Park, Jeonghyun; Hashimoto, Tomoki; Lee, Jae-Woo
Abstract: Activation of mast cells participates in the chronic inflammation associated with cerebral arteries in intracranial aneurysm formation and rupture. Several studies have shown that the anti-inflammatory effect of mesenchymal stem cells (MSCs) is beneficial for the treatment of aneurysms. However, some long-term safety concerns exist regarding stem cell-based therapy for clinical use. We investigated the therapeutic potential of microvesicles (MVs) derived from human MSCs, anuclear membrane bound fragments with reparative properties, in preventing the rupture of intracranial aneurysm in mice, particularly in the effect of MVs on mast cell activation. Intracranial aneurysm was induced in C57BL/6 mice by the combination of systemic hypertension and intrathecal elastase injection. Intravenous administration of MSC-derived MVs on day 6 and day 9 after aneurysm induction significantly reduced the aneurysmal rupture rate, which was associated with reduced number of activated mast cells in the brain. A23187-induced activation of both primary cultures of murine mast cells and a human mast cell line, LAD2, was suppressed by MVs treatment, leading to a decrease in cytokine release and tryptase and chymase activities. Upregulation of prostaglandin E2 (PGE2) production and E-prostanoid 4 (EP4) receptor expression were also observed on mast cells with MVs treatment. Administration of an EP4 antagonist with the MVs eliminated the protective effect of MVs against the aneurysmal rupture in vivo. Human MSC-derived MVs prevented the rupture of intracranial aneurysm, in part due to their anti-inflammatory effect on mast cells, which was mediated by PGE2 production and EP4 activation. Abstract : Effects of intravenous administration of human mesenchymal stem cells-derived microvesicles (MVs) in the rupture of intracranial aneurysms. (A) Schematic diagram of experimental protocol to examine MVs treatment in a mouse model of aneurysm. (B-D) Incidence of aneurysm formation (unruptured and ruptured) (B), aneurysmal rupture rate (C) and symptom-free curve (Kaplan-Meier analysis curve) (D) were examined within 21 days after aneurysm induction in mice treated with vehicle (phosphate buffered saline) or MVs. In (D), the vertical dash lines indicate the time point of MVs or vehicle administration. Mice with aneurysm-free were excluded from graphs in (C) and (D). (E) Representative pictures of normal brain, unruptured and ruptured aneurysms with the whole view and magnified view at aneurysm site. * p < .01 by Fisher exact test; ** p < .005 by log-rank test.